2022
DOI: 10.1002/er.8620
|View full text |Cite
|
Sign up to set email alerts
|

Designing of Kirkendall effect assisted CoFe : WS 2 nanoboxes for dye‐sensitized solar cell and supercapacitor applications

Abstract: In this study, CoFe: tungsten disulfide (WS 2 ) hollow nanoboxes were synthesized for dye-sensitized solar cell (DSSC) and supercapacitor (SC) applications.Hollow nanoboxes structured as CoFe: WS 2 were synthesized using the facile hydrothermal and co-precipitation methods, combined with the ultrasonication technique as a pioneer. The morphological transformation from nanocubes to hollow nanoboxes (Kirkendall effect) was observed upon the incorporation of WS 2 quantum dots in an optimal ratio. The CoFe: WS 2 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…When two materials of various diffusivity concentrations were combined in the presence of external kinetic energy, the ion diffusion occurs from the higher to lower concentration region owing to the nonequality in their solubility and diffusion rate. 27 Here, when WS 2 / NiFe and rGO are brought into contact under probe sonication, the heterogeneity in the diffusion causes the movement of ions from the high concentration to lower concentration area. Initially, the nickel, iron, and tungsten ions move outward with simultaneous internal diffusion of sulfur ions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When two materials of various diffusivity concentrations were combined in the presence of external kinetic energy, the ion diffusion occurs from the higher to lower concentration region owing to the nonequality in their solubility and diffusion rate. 27 Here, when WS 2 / NiFe and rGO are brought into contact under probe sonication, the heterogeneity in the diffusion causes the movement of ions from the high concentration to lower concentration area. Initially, the nickel, iron, and tungsten ions move outward with simultaneous internal diffusion of sulfur ions.…”
Section: Methodsmentioning
confidence: 99%
“…The evolution of nanocage morphology can be described using the Kirkendall mechanism, Graham’s law of diffusion, and kinetic theory of solids. When two materials of various diffusivity concentrations were combined in the presence of external kinetic energy, the ion diffusion occurs from the higher to lower concentration region owing to the nonequality in their solubility and diffusion rate . Here, when WS 2 /NiFe and rGO are brought into contact under probe sonication, the heterogeneity in the diffusion causes the movement of ions from the high concentration to lower concentration area.…”
Section: Experimental Proceduresmentioning
confidence: 99%
“…However, the structure of molybdenum disulfide is difficult to control during the simple hydrothermal process. 18 The combination of the hydrothermal method and template method may be a suitable method for preparing MoS 2 electrode materials with a hollow structure. 19 Zhang et al 20 reported a two-step template-assisted method to synthesize MoS 2 /PANI hollow microspheres as electrode materials for supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings demonstrate that, by reducing the size of the material to that of QDs, the transportation and diffusion of ions within the material are significantly decreased. 23 Mohammadnezhad et al reported that incorporating lowdimensional nanocarbon, such as graphene, into a CuS composite improves its electrocatalytic properties and subsequently enhances the performance of DSSCs. 24 Akshaya et al 3 investigated WS 2 QDs coated over NiFe nanocube electrode materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Low-dimensional WS 2 electrode materials have been used for supercapacitors with an impressive performance. Their findings demonstrate that, by reducing the size of the material to that of QDs, the transportation and diffusion of ions within the material are significantly decreased . Mohammadnezhad et al reported that incorporating low-dimensional nanocarbon, such as graphene, into a CuS composite improves its electrocatalytic properties and subsequently enhances the performance of DSSCs .…”
Section: Introductionmentioning
confidence: 99%